BENTUK–BENTUK TES DAN KARAKTERISTIKNYA - Achmad Rasyid Ridha; Nabila; Qonita Setyaningsih (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Education must foster the nation's philosophical and cultural values ​​holistically and comprehensively. Therefore, a more in-depth study of education is necessary. Educational institutions often experience problems with students. This is because teachers do not fully understand students' needs. Teachers often act carelessly during the learning process. Teachers often ignore evaluation results in learning. When this occurs, it will cause problems. In regional, national, and international forums, to perform well in international forums, teachers must understand the extent of students' abilities. Teachers need to understand the concepts and procedures for conducting learning evaluations so that student abilities can be detected and then followed up as needed. One way to conduct learning evaluations is through tests. There are many types of tests administered to determine student abilities. Teachers need to understand this so that when they administer tests, they can be targeted and meet needs. If this can be achieved, the learning process will certainly develop and will influence the quality of students.